Evaluating the Efficacy of Approaches to Control Invasive Populations: A Conceptual Model Development for the Signal Crayfish - Sandra Hudina; Ivana Maguire; Paula Dragičević; Nika Galic (Ecologies, 2022)
Invasive crayfish are among the major threats to freshwater ecosystems, with the signal crayfish, Pacifastacus leniusculus, being one of the most successful crayfish invaders in Europe. Approaches to invasive crayfish control range from manual and physical to biological and biocidal control methods. However, all of these approaches have their drawbacks and have limited efficacy. Among traditional approaches with minimal impacts on environment and non-target species, manual control via trapping is the most frequently applied. More innovative approaches comprise, among others, usage of sterile male release technique, whose efficacy in the field is yet to be fully tested, especially how it combines with more traditional approaches. A good alternative to costly and logistically challenging field comparisons of these approaches and their combinations is population modeling. Population models can integrate all relevant species-specific biological and ecological information and can be applied to identify management scenarios of highest impact on invasive crayfish abundances. In this study, we developed a conceptual population model of the invasive P. leniusculus following the Pop-GUIDE framework. In addition, we expanded on the framework to increase its applicability to other fields beyond environmental risk assessment. Finally, we discuss potential application of the model and its future use as a management tool.